Peningkatan Partisipasi Belajar Siswa Kelas IV Dalam Pembelajaran PAI Dengan Strategi True or False Di SDN 38 Sungai Limau Kabupaten Padang Pariaman - Hasnibar Hasnibar (Indonesian Institute for Counseling, Education and Therapy (IICET), 2016)
This research is based on the lack of student’s participacion in learning religion subject, including do discussion, propose the ideas, or conclude the material. It is caused by “speech method” that teacher used to do in learning, so that students got the low score for this subject. This research is aimed to improve student’s participation in learning religion subject by implementing True of False method. This is classroom action research with subject are students grade IV in SDN 38 Sungai Limau Kabupaten Padang Pariaman. Data were obtained through observation on student’s participation in learning, observation on teacher’s activities, and final test for students. Data were analyzed quantitatively and qualitatively. Based on the result of this research, student’s participation in learning: (1) percentage of students in doing discussion is 60% for cycle I and 85% for cycle II; (2) percentage of students in proposing ideas is 50% for cycle I and 75% for cycle II; and (3) percentage of students in concluding the lesson is 30% for cycle I and 72.5% for cycle II. Thus, learning of religion subject that implement the True or False strategy can improve student’s participation in learning.